POLA PERILAKU HIDUP SEHAT TERHADAP KESEJAHTERAAN SANTRI MA’HAD UIN WALISONGO SEMARANG - Rima Qoriah; Susanti Susanti; Indah Nur Haliza; Ahmad Fauzan Hidayatullah (J-KESMAS: Jurnal Kesehatan Masyarakat, 2020)
The pattern of healthy living is a behavior practiced by every individual with his awareness to improve his health and participate actively in creating a healthy environment. In this case, the authors use the literature review method to refer to journals about healthy behavior patterns and conduct interviews. This study aimed to determine the relationship of healthy behavior patterns seen from the aspect of religion (religious teachings). The results showed that the environment and behavior are the biggest factors that can influence healthy lifestyles. Just as when we live in an environment that is less aware of environmental cleanliness, we will also be influenced to tend to do the same thing with the behavior of the majority of people around us. Conversely, if we live in an environment with high environmental awareness, such as diligently carrying out clean Friday activities, we will also be influenced by the nature of being more positive in our daily behavior. Then the behavior of healthy living will be good and have a good impact on survival